Penambahan Kompos Baru Campuran Kiapu Dan Jerami Padi Pada Media Sisa Tanam Periode Pertama Terhadap Pertumbuhan Dan Hasil Tanaman Padi Gogo (Oryza sativa L.) - Masita Indriani; Anis Sholihah; Mahayu Woro Lestari (AGRONISMA, 2019)
This study aims to determine the effect of addition of palm leaf residues (Pistia stratiotes) and new rice straw in various compositions to the growth and yield of second period upland rice plants. The design used was RAK, the treatment (R1 + = 100% kiapu; R2 + = 75% kiapu + 25% rice straw; R3 + = 50% kiapu + 50% rice straw; R4 + = 25% kiapu + 75% rice straw ; R5 + = 100% rice straw) plus NPK treatment and control.f rom the results of the study showed that the mixture of Kiapu compost and rice straw treatment R4 + = 25% kiapu and 75% rice straw had an average variable growth of plant length of 92.33 cm, number of leaves 217.67 pot-1 barley, number of tillers 56.83 pot-1 tillers , and a total root length of 453.60 cm. In the production variable grain weight per hectare which has a good effect on the treatment of R5 + = 100% rice straw is 5.84 tons ha-1.